DISORDER STATE AND DYNAMICS OF IMMUNE RESPONSIVENESS IN EMPLOYEES OF CHEMICAL PRODUCTIONS - G. M. Bodienkova; E. V. Boklazhenko; S. I. Kurchevenko; R. Y. Alekseev (Acta Biomedica Scientifica, 2014)
The state of the immune responsiveness of the employees working at the chemical productions has been analysed in dynamics (after 4 years). This work aimed to assess the changes in the serum content of the IgA, M, G concentrations in the employees in the continuous exposure to the neurotoxicants of different chemical nature. 452 workers males were observed, including 166 employees working at the production of vinyl chloride and polyvinyl chloride (VC and PVC) exposed to the chlorinated hydrocarbons, in this group there were 57 "practically" healthy workers with a working period 12,2 ± 0,7 years, 31 persons with the early neurointoxication manifestations. 134 employees working at the caustic production under conditions of the exposure to mercury, including 19 workers with a mean working period under harmful conditions - 19,18 ± 1,08 years as well as 16 patients with the first revealed diagnosis of chronic mercury intoxication (CMI); 32 persons with a long lasting period of CMI have been examined. 82 employees working at the production of epichlorohydrin (EpCH) and 70 workers from the production of methanol have been also examined. The control group consisted of 47 males who did not expose to the substances with the neurotoxic effects based on the occupation. The comparative change assessment of the immune responsiveness in the employees exposed to the neurotoxicants of different chemical nature has allowed to reveal the differences in the content of the immunoglobulins in dependence on the exposure factor and the development stage of the pathological process. The more expressed changes in the immunoglobulin disbalance were found to occur in the exposure to the metallic mercury vapours of the workers. The prospective examination of the employees exposed to the neurotoxicants after 4years has clearly demonstrated that the continuous exposure to the production factors may lead to the index change, the increase in the disbalance of the immunoglobulins of different trends and the expression degree dependent on the specific character and the character of the neurotoxicant exposed, which may testify the different mechanisms which are known to be the basis for forming the neurointoxications of different etiology.